2019
DOI: 10.1074/jbc.ra119.010036
|View full text |Cite
|
Sign up to set email alerts
|

Serine 474 phosphorylation is essential for maximal Akt2 kinase activity in adipocytes

Abstract: Edited by Alex TokerThe Ser/Thr protein kinase Akt regulates essential biological processes such as cell survival, growth, and metabolism. Upon growth factor stimulation, Akt is phosphorylated at Ser 474 ; however, how this phosphorylation contributes to Akt activation remains controversial. Previous studies, which induced loss of Ser 474 phosphorylation by ablating its upstream kinase mTORC2, have implicated Ser 474 phosphorylation as a driver of Akt substrate specificity. Here we directly studied the role of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 69 publications
3
39
0
Order By: Relevance
“…Interestingly, changes in BCKDHA content profoundly affected AKT2 Ser 474 phosphorylation than on AKT1 Ser 473. Previous studies have reported the importance of AKT2 Ser 474 phosphorylation for maximal activation of AKT and insulin-regulated processes (82).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, changes in BCKDHA content profoundly affected AKT2 Ser 474 phosphorylation than on AKT1 Ser 473. Previous studies have reported the importance of AKT2 Ser 474 phosphorylation for maximal activation of AKT and insulin-regulated processes (82).…”
Section: Discussionmentioning
confidence: 99%
“…Using a compartment‐specific probe for the endogenous mTORC2 activity, it was shown that both the localization and activity of mTORC2 at the plasma membrane are PI3K‐independent and that phosphorylation of Akt in response to growth factors is exclusively triggered by its membrane recruitment . However, it is important to keep in mind that mTORC2 is not absolutely required for Akt activity, though it augments phosphorylation of several Akt‐specific substrates, such as FoxO transcription factors, Tsc2, PRAS40, and AS160 …”
Section: Cellular Control Of Akt Activitymentioning
confidence: 99%
“…Similarly, phosphorylation of the lysosomal Akt substrate GFAP was shown to inhibit chaperone‐mediated autophagy . Furthermore, Akt phosphorylation on S473 could differentially regulate glucose transporters Glut1 and Glut4 in different cell types, suggesting that compartment‐specific phosphorylation dynamics could help define functional outcomes of Akt signaling. These examples demonstrate that cellular membranes could both contribute to local Akt activation kinetics and guide its activity toward compartment‐specific substrates.…”
Section: Cellular Control Of Akt Activitymentioning
confidence: 99%
See 2 more Smart Citations